The positive allosteric modulation of GABAA receptors mRNA in immature hippocampal rat neurons by midazolam affects receptor expression and induces apoptosis. (3rd October 2019) - Sinner, Barbara; Steiner, Julia; Malsy, Manuela; Graf, Bernhard M.; Bundscherer, Anika
Abstract: Background: Numerous experimental studies show that anesthetics are potentially toxic to the immature brain. Even though benzodiazepines are widely used in pediatric anesthesia and intensive care medicine, only a few studies examine the effects of these drugs on immature neurons. Methods: Hippocampal neuronal cell cultures of embryonic Wistar rats (15 days in culture) were incubated with midazolam 100 or 300 nM for either 30 min or 4 h. The time course of the mRNA expression of the glutamate receptors subunits NR1, NR2A and NR2B of the NMDA receptor, the GluA-1 and A-2 subunits of the AMPA receptor as well as the alpha 1 subunit of the GABAA receptor were examined by PCR. Apoptosis was detected using Western blot analysis for BAX, Bcl-2 and Caspase-3. Results: Midazolam at 100 and 300 nM applied for 30 min and 100 nM for 4 h affected glutamate receptor and GABAA receptor subunit expression. However, these effects were reversible within 72 h following washout. When 300 nM midazolam was applied for 4 h a significant increase in the NR 1 and NR 2A mRNA subunit expression could be detected. The increase in NR 2B receptor subunit expression as well as the GluA1 subunit expression was not reversible within 72 h following washout. This increase in mRNA glutamate receptor subunit expression was associated with a significant increase in neuronal apoptosis. Conclusion: In immature neurons midazolam altered GABA and glutamate mRNA receptor subunit expression. Prolonged increase in midazolam-induced glutamate receptor expression was associated with apoptosis.